2020
DOI: 10.1080/0951192x.2020.1815844
|View full text |Cite
|
Sign up to set email alerts
|

Design method of human–industrial robot collaborative workstation with industrial application

Abstract: How to design Human-Industrial Robot Collaborative (HIRC) workstations is one of the key challenges in the realisation of safe and efficient HIRC systems in industry. The aim of this paper is to present a simple method to be used in early phases of HIRC workstation design. The design method requires a simulation tool and is based on systematic design methodologies and its reference work, Pahl and Beitz´s engineering design framework. The proposed HIRC design method consists of four phases: planning and clarify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…They focused in particular on safety, ergonomics, time, and performance. Although [35][36][37][38] look in the same direction as the current work, they do not place enough emphasis on the safety aspect. In [39], the authors focus their work on the safety for human operators.…”
Section: State Of Artmentioning
confidence: 88%
See 1 more Smart Citation
“…They focused in particular on safety, ergonomics, time, and performance. Although [35][36][37][38] look in the same direction as the current work, they do not place enough emphasis on the safety aspect. In [39], the authors focus their work on the safety for human operators.…”
Section: State Of Artmentioning
confidence: 88%
“…The approach does not consider compliance with the reference standard in the decision making framework. Ore et al [36] identified the lack of methods supporting efficient HRC workstation design. They propose a step-by-step method useful in the early phases of the workstation design in the context of the Human-Industrial Robot Collaboration (HIRC).…”
Section: State Of Artmentioning
confidence: 99%
“…Fetcher et al (Fechter, Seeber, and Chen 2018) attach this mismatch to missing planning and design tools for collaborative workplaces. Ore et al (2020) claim that one of the main reasons for the shortage of HRC industrial applications is related to the lack of detailed guidelines and structured methods that lead engineers in each step of the collaborative work cell design. Land et al (2020) also pointed out the lack of guidelines and proposed a framework for the HRC development based on virtual simulation.…”
Section: Challenges For Hrc Industrial Applicationsmentioning
confidence: 99%
“…The use case was the collaborative assembly of the seat of custom-made pedal cars, which in reality is used as an actual training scenario at a truck manufacturer. The simulation was programmed within the software IPS IMMA (Ore et al, 2020). The video showed the HRC from a bird's eye view.…”
Section: Task and Apparatusmentioning
confidence: 99%